Phenytoin and Neuropsychological Performance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A comprehensive neuropsychological assessment of young adults (mean age 32) before and after treatment with phenytoin (PHT) for a 5 year study period is reported from the Regional Epilepsy Center, University of Washington School of Medicine, Seattle, Washington.